Search for production of [Formula: see text] resonances decaying to a lepton, neutrino and jets in [Formula: see text] collisions at [Formula: see text] TeV with the ATLAS detector - Aad, G; Abbott, B; Abdallah, J; Abdel Khalek, S; Abdinov, O; Aben, R; Abi, B; Abolins, M; AbouZeid, O S; Abramowicz, H; Abreu, H; Abreu, R; et al. (The European physical journal. C, Particles and fields, 2015)
A search is presented for narrow diboson resonances decaying to [Formula: see text] or [Formula: see text] in the final state where one [Formula: see text] boson decays leptonically (to an electron or a muon plus a neutrino) and the other [Formula: see text] boson decays hadronically. The analysis is performed using an integrated luminosity of 20.3 fb[Formula: see text] of [Formula: see text] collisions at [Formula: see text] TeV collected by the ATLAS detector at the large hadron collider. No evidence for resonant diboson production is observed, and resonance masses below 700 and 1490 GeV are excluded at 95 % confidence level for the spin-2 Randall-Sundrum bulk graviton [Formula: see text] with coupling constant of 1.0 and the extended gauge model [Formula: see text] boson respectively.